Analysis of Genetic Diversity of Yangzhou Chicken by Microsatellite Markers - Liu, G.Q.; Jiang, X.P.; Wang, J.Y.; Wang, Z.Y.; Liu, G.Y.; Mao, Y.J. (International Journal of Poultry Science, 2008)
Genetic variation at 20 microsatellite loci and genetic diversity were examined for Yangzhou Chicken. Observed and effective number of alleles across the microsatellite loci varied from 2-6 with an overall mean of 3.778 and 2.404, respectively. Observed and effective heterozygosity varied from 0.129-0.755 with an average of 0.422 and 0.517, respectively. Average polymorphism information content was 0.464. The genetic structure indicated that Yangzhou Chickens have substantial genetic variation. Population showed fairly high level of inbreeding (Fis = 0.184) and global heterozygote deficit. The allele frequency distribution is displayed an L shape, suggesting that no recent bottleneck affecting the genetic variability occurred. The information generated in this study will greatly aid in the establishment of effective breeding strategies for Yangzhou Chicken and may further be utilized for studying differentiation and relationships among different chicken breeds.